PERAN KELUARGA DAN LINGKUNGAN SOSIAL DALAM MENCEGAH PERKAWINAN USIA DINI DI KECAMATAN BANJARMASIN SELATAN - Mukhsin Aseri (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2023)
This study aims to analyze the role of family and social environment in preventing early marriage in South Banjarmasin District. A qualitative approach was used with data collection techniques in the form of in-depth interviews with three informants, namely teenagers who have experienced early marriage, parents or guardians of teenagers who have married at an early age, and the Head of South Banjarmasin Sub-district. The interview data was analyzed using the data reduction method to identify the main themes related to the role of family and social environment in the phenomenon of early marriage. The results showed that family pressure and social norms in the neighborhood influence teenagers' decision to marry at an early age. Parents or guardians think that marriage will provide protection and stability for their children in difficult economic situations. The local government has initiated sexual education programs in schools and provided counseling services for adolescents, as well as collaborating with non-governmental organizations in socialization campaigns on the dangers of early marriage.